2015
DOI: 10.1002/mgg3.155
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory variant inFZD6gene contributes to nonsyndromic cleft lip and palate in an African‐American family

Abstract: Nonsyndromic cleft lip with or without cleft palate (NSCLP) is a common birth defect affecting 135,000 newborns worldwide each year. While a multifactorial etiology has been suggested as the cause, despite decades of research, the genetic underpinnings of NSCLP remain largely unexplained. In our previous genome-wide linkage study of a large NSCLP African-American family, we identified a candidate locus at 8q21.3-24.12 (LOD = 2.98). This region contained four genes, Frizzled-6 (FZD6), Matrilin-2 (MATN2), Odd-sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…We hypothesized that additional RVs in this region are associated with bIMT. Indeed, our candidate gene re-sequencing study, as well as other recent studies, have shown that sequencing regions under linkage peaks can successfully identify RVs influencing complex traits and disorders[16,2225], particularly in extended families. Extended families are well-suited for the identification of RVs for several reasons including: 1) Pedigrees may be enriched for individual RVs, making them easier to study[26,27] and 2) Co-segregation of an RV with the trait can be examined to help differentiate between causal and non-causal RVs[26,27].…”
Section: Introductionmentioning
confidence: 73%
“…We hypothesized that additional RVs in this region are associated with bIMT. Indeed, our candidate gene re-sequencing study, as well as other recent studies, have shown that sequencing regions under linkage peaks can successfully identify RVs influencing complex traits and disorders[16,2225], particularly in extended families. Extended families are well-suited for the identification of RVs for several reasons including: 1) Pedigrees may be enriched for individual RVs, making them easier to study[26,27] and 2) Co-segregation of an RV with the trait can be examined to help differentiate between causal and non-causal RVs[26,27].…”
Section: Introductionmentioning
confidence: 73%
“…For instance, López Rodríguez et al identified SNPs in a FOXA2-regulated transcriptional enhancer at a type 2 diabetes intronic locus that controls GCKR expression in liver cells [31]. For NSCL/P, Cvjetkovic et al identified an SNP in intron 1 of FZD6 that creates an allele-specific protein-binding site and decreases promoter activity, which is involved in craniofacial development and contributes to NSCL/P by perturbing the WNT signaling pathway [18]. Before the GWAS of NSCL/P, the NTN1 gene in the chromosome 17p13 region was not associated with NSCL/P susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…1d). MMP2 and FOS have previously been shown to interact in studies that demonstrate that the inhibition of MMP2 suppresses the induction of c-FOS and both of these genes are activated in metastatic gastric adenocarcinoma [13,63]. FOS, which has been shown to play a role in cellular functions including apoptosis, is a target for CASP8 [64].…”
Section: Discussionmentioning
confidence: 99%